An Updated Meta-Analysis of the Efficacy and Safety of Prostatic Artery Embolization vs. Transurethral Resection of the Prostate in the Treatment of Benign Prostatic Hyperplasia - Xu, Zhunan; Zhou, Zhongbao; Mu, Yingmei; Cai, Tong; Gao, Zhenli; Liu, Lingling (Frontiers in Surgery, 2021)
Background: Prostatic artery embolization (PAE) in the treatment of benign prostatic hyperplasia (BPH) has been introduced into clinical practice, but conclusive evidence of efficacy and safety has been lacking. Objective: To comparing efficacy and safety of prostatic artery embolization (PAE) versus transurethral resection of prostate (TURP), we performed a meta-analysis of clinical trials. Methods: We searched randomized controlled trials (RCTs) from Pubmed, Embase, Wanfang and CNKI from January 2000 to December 2020 and used RevMan 5.0 to analyse the data after five RCTs were included. Results: The reducing of prostate volume (PV) (Median mean (MD) 14.87; 95% confidence interval (CI) 7.52-22.22; P<0.0001) and the increasing of maximum flow rate in free uroflowmetry (Qmax) (MD 3.73; 95% CI 0.19-7.27; P=0.004) were obvious in TURP than in PAE; however, the rate of lower sexual dysfunction (odds ratio (OR) 0.12; 95% CI 0.05-0.30; P<0.00001) was lower in PAE compared with TURP. Meanwhile, no conspicuous difference in International Prostate Symptoms Score (IPSS) score (MD 1.42; 95% CI -0.92-3.75; P=0.23), quality of life (Qol) score (MD 0.21; 95% CI -0.31-0.73; P=0.43), post void residual (PVR) (MD 21.16; 95% CI -5.58-47.89; P=0.12), prostate-specific antigen (PSA) (MD 0.56; 95% CI -0.15-1.27; P=0.12) and complication (OR 0.90; 95% CI 0.20-4.05; P=0.89) between PAE and TURP group was showed. Conclusion: PAE may replace TURP as an alternative treatment for Benign prostatic hyperplasia (BPH) patients who don’t want to have surgery or with operational contraindications.